Diagnosing the Quality of Workplaces Using the Fuzzy Set Methods - Michalski, Włodzimierz (Studia Oeconomica Posnaniensia, 2013)
This article aims to present the essence of a safety culture and safety climate as a source of competitive advantage. For this purpose, it defines the term safety culture and demonstrates that a safety culture is an element of organizational culture as well as a strategic business objective. The article shows that a safety culture can be monitored through research into the safety climate. The issues, considerations and conclusions presented in this article are based on studies of the literature.